UM FRAMEWORK DE SEGURANÇA BASEADO EM ENGENHARIA DIRIGIDA POR MODELOS PARA PLATAFORMAS DE COMPUTAÇÃO EM NUVEM: Uma Abordagem para Modelos SaaS. - MATOS, Pablo Luís Castro de (2015)
The development and use of software based on cloud computing have been highlighted more and more nowadays. Software as a Service (SaaS) has been considered as a trend for small, medium and large companies, subtly acquiring presence in personal computing too. This service popularizing brings with it many challenges concerning to information security handled by their suppliers and the vulnerability of their applications. In this work, we propose a SaaS development framework by combining the Model-Driven Engineering (MDE) with merging techniques of domain-security models and domainapplication model. This approach involves the use of MDE techniques for achieving such adaptation and assist in the software development process. By adopting the MDE approach, it is possible to combine elements of different models, from source models reaching a target model by using weaving techniques. A prototype implements the proposed framework and reuses the Mapping Tool for Model Driven Engineering (MT4MDE) and Semi-Automatic Matching Tool for Model Driven Engineering (SAMT4MDE) in order to demonstrate the used methodology. The results demonstrate the feasibility and benefits of combining several security aspects in the development process of SaaS.